Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/jssc.200500292
|View full text |Cite
|
Sign up to set email alerts
|

Application of 1-alkyl-3-methylimidazolium-based ionic liquids in separation of bioactive flavonoids by capillary zone electrophoresis

Abstract: Room-temperature ionic liquids (ILs) are liquids that are constituted entirely of ions and can provide a solvent environment quite unlike any other available at room temperature. They continue to attract considerable interest in the chemistry research community as they are good solvents for a wide range of both inorganic and organic materials. In this study, a CZE method has been established for resolving natural flavonoids, quercetin, kaempferol and isorhamnetin in the Chinese herbal extract from Hippophae rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…A CZE method was established for resolving natural flavonoids in a Chinese herbal extract using 1-alkyl-3-methyl-imidazolium-based ionic liquids as additives [197]. Baseline separation, high efficiencies, and symmetrical peaks were obtained for the flavonoids.…”
Section: Capillary Electrophoretic and Capillary Electrochromatographmentioning
confidence: 99%
See 1 more Smart Citation
“…A CZE method was established for resolving natural flavonoids in a Chinese herbal extract using 1-alkyl-3-methyl-imidazolium-based ionic liquids as additives [197]. Baseline separation, high efficiencies, and symmetrical peaks were obtained for the flavonoids.…”
Section: Capillary Electrophoretic and Capillary Electrochromatographmentioning
confidence: 99%
“…Electropherograms of (A) a mixture of flavonoids, (B) an extract of Hippophae rhamnoides and (C) an extract of medicinal preparation, Sindacon tablet, using 1-alkyl-3-methyl-imidazolium-based ionic liquids, as the additive in 20 mM borate buffer, pH 10. 1: IS, isorhamnetin; 2: KA, kaempferol; 3: QU, quercetin [197].…”
Section: Capillary Electrophoretic and Capillary Electrochromatographmentioning
confidence: 99%
“…The other application of RTILs was related to the stationary phase [14] or the solvent for stationary phase [15] in GC. In CE, mostly researches were centralized in using RTILs as the analytes [16][17][18][19][20][21][22] or additives [23][24][25][26][27][28][29]. People had confirmed the addition of RTILs in electrolytes ameliorated the electrophoretic separation.…”
Section: Introductionmentioning
confidence: 99%
“…It had been found that the migration times of the analytes attributed to the positive charged groups coating on the inner surface of capillary and the free ions in bulk solution [21] in CE. As the additives in EKC, some surfactants of RTILs were applied to achiral and chiral separation of binaphthyl derivatives [23] and determine bioactive flavonoids [29]. Several novel chiral ionic liquids were synthesized for micellar elctrokinetic chromatography to improve the separation [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The application of IL in analytical chemistry has also attracted considerable attention, such as microextraction [22], sensors [23], MALDI-MS [24], chromatography [25], and so on. Until recently, several research groups have reported the utility of IL as buffer modifiers, BGE and dynamic coating agent in CE to achieve better selectivities [26][27][28][29][30]. As wall permanent coating materials, their use for CEC was extensively investigated for the separation and determination of metal cations [31,32], Sildenafil metabolites [33], DNA [34] and alkylphosphonic acids/monoesters [35] etc.…”
Section: Introductionmentioning
confidence: 99%